Pomen barierne funkcije za zdravje naše kože - Zvonar Pobirk, Alenka (Farmacevtski vestnik, 2021)
The skin is our largest organ, fulfiling different functions. It serves as our primary defence sytem, regulating the exchange of substances with surounding environment and protecting our body from various external factors. Effective epidermal barrier, which is cruical for the health of the skin and the entire body, resides predominantly (around 90 %) in the outermost skin layer - stratum corneum. The stratum corneum with its interconnected corneocyte embedded in a cornified envelope, and intercellular highly structured lipid bilayers largely controls the transcutaneous absorption of xenobiotics and regulates the transcutaneous water loss through the skin surface. Herein the mechanisms involved in barrier homeostasis regulation are presented, together with some disorders increasing the risk for the development of various (inflammatory) skin diseases. Selected non-invasive methods suitable for n vivo monitoring of various skin parameters related to skin barrier function are presented briefly. They found their use in early diagnosis and monitoring of the therapy effectiveness, and have important role in the development and efficacy evaluation of new dermal products.
Keywords: barierna funkcija; diferenciacija keratinocitov; Koža; lipidi; pH kože